214 THE IMPACT OF ARRHYTHMIA ON PROGNOSIS IN HOSPITALIZED COVID-19 PATIENTS. A CARDIAC TELEMETRIC MONITORING STUDY. (15th December 2022) - Cozzolino, Domenico; Romano, Ciro; Marrone, Aldo; Nevola, Riccardo; Aprea, Concetta; Ruocco, Rachele; Cirigliano, Giovanna; Catalini, Christian; De Zenise, Maria Schiano; Adinolfi, Luigi Elio
Abstract: Background: Cardiovascular abnormalities have been largely reported in patients with COVID-19. Among these, myocardial injury and rhythm disorders represent one of the most important complications in patients affected by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection. Moreover, a poorer prognosis has been documented in COVID-19 patients when complicated by arrhythmias, independently by age and sex. Objectives: The aims of the present study were to identify some of non-cardiac and cardiac comorbidities and some myocardial electrical features (including QT dispersion) associated with arrhythmia in hospitalized COVID-19 patients. Moreover, another objective was to contribute in analyzing the impact of arrhythmias on outcome in this setting of patients. Methods: At admission, each patient underwent cardiac telemetry monitoring through entire hospitalization period. In all the subjects, laboratory analyses, standard 12-lead electrocardiogram (both at admission and on discharge), and lung imaging examination (by means of both ultrasound scans and computed tomography) were performed. Patients exhibiting arrhythmia during in-hospital period were divided into three groups: i, with brady-arrhythmias; ii, with tachy-arrhythmias; and, iii, with tachy- and brady-arrhythmias. Results: Two-hundred patients completed the study (males, 123; mean age, 70.1 years); of these, 80 patients (40%) exhibited rhythm disorders on cardiac telemetry. Patients with arrhythmia resulted to be older (p<0.0001) than patients without arrhythmia. Moreover, patients with arrhythmia showed: i, greater number of comorbidities (p<0.0001); ii, higher values of creatinine (p=0.007), B-type natriuretic peptide (p<0.0001), troponin (p<0.0001), c-reactive protein (p=0.01), ferritin (p=0.001), d-dimer (p<0.0001), and procalcitonin (p=0.0008); iii, QT interval (p=0.002), QTc interval (p=0.04), and QTc dispersion (p=0.01); and, iiii, lower values of sodium (p=0.03), magnesium (p=0.04), glomerular filtration rate (p<0.0001), and hemoglobin (p=0.008) as compared to patients without arrhythmia. By comparing the three subgroups of patients, no significant differences were found. Multivariate analysis showed that age (OR=1.14 [95% CI: 1.07-1.22]; p=0.0004), coronary artery disease (OR=12.7 [95% CI: 2.38-68.01]; p=0.005), and circulating troponin (OR=1.05 [95% CI: 1.003-1.10]; p=0.04) represented risk factors independently associated with arrhythmia. By analyzing all-cause in-hospital mortality, it resulted a ∼forty-fold higher among patients with arrhythmia (OR=39.66 [95% CI: 5.20-302.51]; p=0.0004) when compared to patients without rhythm disorders. Conclusion: In the present study, a rrhythmias have been to be associated with ageing, coronary artery disease, subtle myocardial injury, hyperinflammatory status, coagulative unbalance, and abnormalities in myocardial electrical impulse propagation in patients affected by SARS-CoV-2 infection. In alignment with previous reports, the presence of arrhythmia seems to be associated with a worse in-hospital prognosis. Given its usefulness, routinary use of cardiac telemetric monitoring should be encouraged in COVID wards.